PENGARUH KOMPETENSI GURU, DISIPLIN SISWA DAN SARANA MEDIA PEMBELAJARAN TERHADAP EFEKTIVITAS PEMBELAJARAN DI SMK FARMASI SARASWATI DENPASAR - Astuti, Ni Wayan Widi (Widyadari : Jurnal Pendidikan, 2019)
Entering the globalization era, education in Indonesia must follow competitive changes. All fields experienced shifts and challenges including educational institutions. Educational institutions will continue to experience changes and developments following the rapid development of information technology due to the influence of the entry of globalization era. The global demand demands the world of education to always adjust the development of technology to efforts in improving the quality of education. Many problems in the world of education include those related to the quality of education, such as the quality of graduates, the quality of teaching, and the quality of professionalism and teacher performance. It is also inseparable from leadership management, limited funds, facilities and infrastructure, educational facilities and media, resources, tools and materials, school climate, educational environment, and support from relevant parties. The purpose of the study was to determine and analyze the effect of teacher competence on the effectiveness of learning at the Pharmacy Pharmacy at Saraswati Denpasar. Denpasar. Teacher competency t test results obtained a significance level of 0.048 which is smaller and a significance of 0.05 means that teacher competence has a positive and significant effect on the effectiveness of Class X vocational pharmacy students in Denpasar. The results of this study were supported by the research. The results of the student discipline t test were obtained by obtaining a significance level of 0.004 which was smaller and significance = 0.05, meaning that student discipline had a positive and significant effect on the learning effectiveness of Class X students of SMK Saraswati Pharmacy Denpasar. The results of the t test of media facilities learning obtained significance level of 0.046 which is smaller and significance = 0.05 means the learning media means a positive and significant effect on learning effectiveness